Metallic Nanoislands: Metallic 3D Random Nanocomposite Islands For Near‐Field Spatial Light Switching (Advanced Optical Materials 10/2018). Issue 10 (May 2018) - Son, Taehwang; Moon, Gwiyeong; Lee, Hongki; Kim, Donghyun
Abstract : In article number1701219, Donghyun Kim and co‐workers report near‐field characteristics of metallic nanocomposite islands produced by spatial switching of light. The nanoislands produce strongly amplified super‐localized light by plasmonic matching. The localized light was found to displace almost linearly and rotate with a near‐field coverage close to 90% by 10‐channel switching. From experimental demonstration, this study opens the possibility of nanoislands for super‐resolution microscopy and molecular detection.